Synthesis, antibacterial activity and docking studies of chloroacetamide derivatives - Murtaza, Shahzad; Altaf, Ataf Ali; Hamayun, Muhammad; Iftikhar, Kiran; Tahir, Muhammad Nawaz; Tariq, Javaria; Faiz, Khadija (European Journal of Chemistry, 2019)
Structural modification of lead compounds is a great challenge in organic synthesis. Introduction of different functional groups not only modify the structure of starting material but also improve their biological activeness. Small synthetic molecules are favored in spite of the reality that majority of drug molecules derived from natural sources, are in vogue. In the present work, acetamide derivatives were synthesized using chloroacetyl chloride. After synthesizing targeted series of acetamide derivatives these compounds were further modified using different amines including 2-aminobenzene thiol, benzyl amine, benzene 1,4-diamine, 4-amino-1,5-dimethyl-2-phenyl-1H-pyrazol-3(2H)-one, 4-aminophenol, hydrazine and 4-amino-N-(5-methylisoxazol-3-yl)benzenesulfonamide. All of these synthesized compounds were characterized by FT-IR, 1H NMR, 13C NMR and X-ray crystallography. The compounds were assessed for their anti-bacterial activity using disc diffusion method against Staphylococcus aureus and Escherichia coli. The compounds were found to exhibit comparable activity to the standard drug used. This was further supported by molecular docking studies using bacterial DNA gyrase and Topoisomerase II targets causing bacterial death as they are major bacterial proteins known to be involved in transcription and replication process. Results proved that the compound 2b was the most efficacious antimicrobial compound among the synthesized set of compounds. To tackle the growing drug resistance acetamide based functionalities can be regarded as the active lead compounds to target different drug resistance microorganism.